Comparision of IMT GT: Study Case of Malaysia-Thailand and Indonesia - Rakhmadi, Roby; Hutagalung , Simon Sumanjoyo; Nizar, Moh (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to analyze the dynamics of subregional political economy in Southeast Asia through a case study of cooperation between Indonesia, Malaysia, and Thailand within the framework of the Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT). IMT-GT is a subregional cooperation initiative that aims to accelerate economic development in the border areas of the three countries by optimizing the potential of areas that have been underdeveloped. This study uses a qualitative approach with descriptive analysis to examine the comparison of IMT-GT in Indonesia and Malaysia in increasing regional economic growth, identifying the challenges faced, and assessing its impact on regional economic integration in Southeast Asia. The results of the study indicate that there are differences in the implementation of IMT-GT in Indonesia and Malaysia as well as several obstacles that hinder the implementation of IMT GT in the countries concerned. This study also highlights the importance of the role of IMT-GT in strengthening connectivity and encouraging inter-regional trade. The policy implications of this study are the need to increase synergy between the government and the private sector, as well as strengthening subregional institutions to maximize the benefits of IMT-GT cooperation.